A HPF AC-AC converter for Permanent Magnet Generator applications - Godoy, R. B. [UNESP]; Pires, G.; Portela, M.; Fernandes, R. [UNESP]; De Seixas, F. [UNESP]; Melo, G. [UNESP]; Canesin, C. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper describes the design and development of a high input power-factor (HPF) AC to AC converter for naval applications using Permanent Magnet Generator (PMG). The proposed converter comprises an isolated three-phase uncontrolled multipulse rectification stage directly connected to a single-phase inverter stage, without the use of DC to DC intermediary stage, resulting in more simplicity for the overall circuitry, assuring robustness, reliability and reduced costs. Furthermore, the multipulse rectifier stage is capable to provide high power factor and input currents with low total harmonic distortion (THD). The output voltage of the PMG varies from 260V rms (220 Hz) to 380V rms (360 Hz), depending on load conditions. The output single-phase inverter stage was designed to operate with wide range of DC bus voltage, maintaining 120V rms, 60 Hz output. Measured total harmonic distortion for the AC output voltage represents less than 2%, at 3.6kW nominal linear load. © 2010 IEEE.
Keywords: AC to AC converter; High input power-factor converter; Permanent Magnet Generator; Power quality; AC-AC converters; Ac-to-ac converter; DC-bus voltages; Design and Development; High input power; High power factor; Input current; Linear loads; Load condition; Multi-pulse rectifiers; Multipulses; Naval applications; Output voltages; Reduced cost; Single-phase inverters; Total harmonic distortions; AC generator motors; Electric power factor correction; Harmonic distortion; HVDC power transmission; Magnetic devices; Permanent magnets; Power electronics; Wave filters; Electric rectifiers